PENGARUH TEMPERATUR TERHADAP SIFAT MEKANIK PADA BAJA KARBON SEDANG ST 60 - ., Lagiyono; ., Suwandono; Masykur, Mukhamad (ENGINEERING, 2011)
Medium carbon fertilizer ST 60 in general is often used in construction of building materials and a variety of fields. Society prefers medium carbon fertilizer because this material is more easily available and relatively affordable  prices, and also the strength and tenacity are sufficient. Temperature significantly affects the mechanical properties of carbon steel is ST 60.  Formulating of the problem in this study is to determine how the mechanical properties of medium carbon steel ST 60 to temperature 00C, 260C, 500C, 1000C. The purpose of this research to know how much testing on tensile strength, hardness, and price impact. The results of research on testing with 00C yield of 696,68 N/mm2tensile test, hardness test of 201,00 HB, the impact test produces 30,35 J/cm2. In the test with a temperature of 260C produced by 694,47 N/mm2tensile test, hardness test of 200,11 HB, the impact test at 24,52 J/cm2. In the test with a temperature of 500C produced by 685,87 N/mm2tensile test, hardness test of 198,00 HB, the impact test at 41,70 J/cm2. In the test with a temperature of 1000C resulted N/mm2tensile test at 672,89 N/mm2, the hardness  of 195,56 HB, the impact test at 37,69 J/cm2. Data analysis in this study using the product moment correlation test and t-test.  The conclusion of this research is that there is a negative relationship between temperature with mechanical properties which means the higher the temperature the more down the value of tensile strength, hardness, and the price impact.Keywords: fertilizer, mechanical, temperature.